Intertemporal Labor Supply Effects of Tax Reforms - Peter Haan (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
In the year 2000, the German government passed the most ambitious tax reform in post-war German history aiming at a significant tax relief for households. One central aim of this tax reform was to improve work incentives and, thereby, foster employment. In this paper, I estimate an intertemporal discrete choice model of female labor supply that allows to analyze the behavioral effects of the tax reform on the labor supply of married and cohabiting women over time. Using the Markov chain property, I analyze the dynamics of labor supply behavior and derive the short- and long-run labor supply effects of the tax reform.
Keywords: C33; J22; H31; H24; 330; Intertemporal Labor Supply of Married Women; Tax reform; Panel Data; Microsimulation.; Einkommensteuer; Steuerreform; Steuerwirkung; Frauenerwerbstätigkeit; Arbeitsangebot; Zeitpräferenz; Deutschland